Isolation of rice endophytic bacterial strain VY81 and study on its bioactive compound antagonizing the phytopathogen Dickeya zeae - Duy Toi, Nguyen; Ngoc Mai, Dinh Thi; Hieu Thu, Nguyen Thi; Tien Dat, Nguyen; Nhu Thao, Nguyen Kim; Thuy Hang, Dinh (Vietnam Journal of Biotechnology, 2022)
The bacterial communities performing endophytic lifestyle have been proven to possess a number of characteristics useful to host plants and thus are considered as “plant probiotics”. Many probiotic bacteria were reported for antagonism against different plant pathogens, including bacteria, fungi, and nematodes. The use of endophytic bacteria as biocontrol agents would have great potentials, allowing reducing the use of agrochemicals and thus support a sustainable agriculture. In this study, endophytic bacteria isolated from rice plants of IR4625 cultivar from Long An province, Vietnam were used for screening strains that have antagonistic activity against Dickeya zeae (Dz), the bacterium causing foot rot disease. The rice plants had foot rot disease symptoms, i.e. dark-brown foot with odor smell typical for bacterial infection. Strain VY81 was isolated from a surface sterilized rice stem sample adjacent to the foot rot area. The crude extract of strain VY81 showed significant antagonistic activity against Dz, with the inhibition zone of 14,25 mm ± 1,06 in diameter. Strain VY81 produced the compound antagonizing Dz at maximal level after 48 h cultivated in TSB medium. The activity was found mainly in the culture broth, just a small part was found intracellularly. The bioactive compound antagonizing D. zeae produced by strain VY81 was purified by HPLC and analyzed by mass spectrometry and NMR spectroscopy. The compound was identified as a quinoline alkaloid, the chemical formula is C17H21ON with chemical name 2-(2-heptenyl)-3-methyl-4(1H)-quinolone. Comparative analyses of the 16S rDNA gene sequence revealed that strain VY81 belonged to the genus Burkholderia, most closely related to Burkholderia cepacia (99,77% sequence homology). The 16S rDNA sequence of strain VY81 was deposited at GenBank under accession number MW056196. Strain VY81 and its quinolone compound would have application potential for development of biocontrol product against the foot rot disease caused by Dickeya zeae.